Analysing the Impacts of Artificial Intelligence Service Quality and Human Service Quality on Customer Satisfaction and Customer Loyalty in the Hospitality Sector. - Jatin Sardesai, Semele; Dsouza, Edgar; Govekar , Supriyanka (Turizam, 2024)
This study explores the differential role of artificial intelligence (AI) and human interface (HI) in the hospitality industry and their impact on customer satisfaction and loyalty. In response to intense competition, the industry is increasingly adopting advanced technologies such as AI and artificial intelligence robotics (AIR) to enhance customer service and improve the overall experience. The primary objective of this research is to investigate how hotel visitors perceive AI service quality and human service quality and how these perceptions influence consumer satisfaction and loyalty. Drawing on previous research by Prentice et al. (2020), the study reveals a positive and significant relationship between AI service quality, human service quality, and customer satisfaction. This contributes to the existing knowledge on the use of AI in the hotel sector and provides valuable insights for future research. Additionally, the study demonstrates that customer satisfaction acts as a mediator between both human service quality and AI service quality and customer loyalty. Importantly, the indirect effect is stronger for human service quality compared to AI service quality, highlighting the need to strike a suitable balance between AI efficiency and human empathy. The findings underscore the potential of AI-powered services to enhance customer satisfaction and operational effectiveness within service organizations. However, the study emphasizes the continued significance of employee service in shaping customer experiences in the service-dominant era. By understanding the potential benefits and challenges associated with AI adoption, organizations can make informed decisions and develop effective strategies for integrating AI technologies. This research contributes to the advancement of AI implementation in the hospitality industry, leading to improved business performance and enhanced customer experiences.
Keywords: AI Service Quality, Human Service Quality, Hospitality, SEM, Customer Satisfaction, Customer Loyalty